What is Type-Safe Code Reuse? - Palsberg, Jens; Schwartzbach, Michael I. (DAIMI Report Series, 1990)
Subclassing is reuse of class definitions. It is usually tied to the use of class names, thus relying on the order in which the particular classes in a program are created. This is a burden, however, both when programming and in theoretical studies. This paper presents a structural notion of subclassing for typed languages. It is a direct abstraction of the SMALLTALK interpreter and the separate compilation technique of MODULA. We argue that it is the most general mechanism which can be supported by the implementation while relying on the type-correctness of superclasses. In short, it captures type-safe code reuse.